2019
DOI: 10.1111/jfpe.13243
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli and Salmonella in liquid egg white by pulsed UV light and its effects on quality

Abstract: This study evaluated the pulsed UV light treatment for the inactivation of Escherichia coli K12 and Salmonella Enteritidis in liquid egg white. Three parameters (treatment time, volume of liquid egg white, and distance from the sample to the pulse UV strobe) have been optimized for log reductions of microorganisms using response surface methodology. The maximum log reductions obtained after 40 s of treatment time at a 5 cm of distance (the energy dose equals 45.6 J/cm 2 ) were 1.28 log CFU/ml of E. coli K12 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…After the PL treatment, the microbial reduction at 5 and 45 s revealed the following results: 1.22 and 2.02 log CFU/cm 2 ( E. coli ), 1.45–2.09 log CFU/cm 2 ( Campylobacter ), and 1.55 and 2.42 log CFU/cm 2 ( Salmonella ). In eggs, Ouyang et al (2019), used PL to inactivate S. Enteritidis inoculated in liquid egg whites. The study reported a significant reduction of 1.98 log CFU/ml after 45.6 J/cm 2 PL treatment.…”
Section: Pl Technologymentioning
confidence: 99%
“…After the PL treatment, the microbial reduction at 5 and 45 s revealed the following results: 1.22 and 2.02 log CFU/cm 2 ( E. coli ), 1.45–2.09 log CFU/cm 2 ( Campylobacter ), and 1.55 and 2.42 log CFU/cm 2 ( Salmonella ). In eggs, Ouyang et al (2019), used PL to inactivate S. Enteritidis inoculated in liquid egg whites. The study reported a significant reduction of 1.98 log CFU/ml after 45.6 J/cm 2 PL treatment.…”
Section: Pl Technologymentioning
confidence: 99%
“…Secondary germicidal mechanisms are a result of longer wavelengths in combination with short pulses that produce localized heating and microvibrations, respectively, that contribute to microbial cell membrane collapse and death ( Sonenshein, 2003 ; Krishnamurthy et al., 2010 ; Cassar et al., 2020 ). In addition to PUV light's antimicrobial effectiveness for numerous other foods, it has also been reported to achieve a significant reduction of Salmonella serotypes on the surface of eggshells ( Hierro et al., 2009 ; Keklik et al., 2010 ; Lasagabaster et al., 2011 ) and in liquid egg ( Ouyang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…After exposure to 2.1 J/cm 2 of PUV light, a 5.0 and 4.9 Log 10 CFU/cm 2 reduction was reported on the surface of washed and unwashed eggs, respectively. Ouyang et al. (2020) used PUV light to inactivate Salmonella Enteritidis inoculated in liquid egg white.…”
Section: Introductionmentioning
confidence: 99%
“…Murray, Wu, Aktar, Namvar, and Warriner (2015) PUV light, which is rich in UV-C light, provides fast microbial inactivation on surfaces using intense light pulses in the wavelength range of 180-1,100 nm (Elmnasser et al, 2007). The efficacy of PUV light to inactivate various spoilage and pathogenic microorganisms on foods continues to be the focus of many recent studies (Chen et al, 2019;Keklik, Elik, Salgin, Demirci, & Koçer, 2019;Ouyang, Demirci, & Patterson, 2020;Preetha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%